Woody and non-woody biomass utilisation for fuel and implications on plant nutrients availability in the mukehantuta watershed in Ethiopia - Bekele, K.; Hager, H.; Mekonnen, Kindu (African Journals Online, 2013)
Plant biomass is a major source of energy for households in eastern Africa. Unfortunately, the heavy reliance on this form of energy is a threat to forest ecosystems and a recipe for accelerated land resource degradation. Due to the increasing scarcity of traditional fuel wood resources, rural communities have shifted to utilisation of crop residues and cattle dung; which otherwise, are resources for soil fertility improvement. The objective of this study was to assess the supply and consumption patterns of fuel biomass and estimate the amount of nutrients that could be lost from burning non-woody biomass energy sources. A survey was conducted in the Mukehantuta watershed in Ethiopia, using a semi-structured questionnaire. An inventory of woody biomass was also carried out on the existing stock in the watershed. Annually, households in the watershed used 1999, 943, 11, 34 and 229 metric tonnes of wood, dung, charcoal, crop residue and tree residues, respectively. The existing wood biomass in the watershed was approximately 292 metric tonnes, implying that consumption exceeds potential supply. As a result of using dung and crop residue biomass for household energy, the watershed, respectively, loses 17.3, 4.3, 20.6, 15.6, 5.4, and 10.2 tonnes of N, P, K, Ca, Mg and Fe nutrients every year. The lost nutrients in terms of fertiliser equivalency are estimated at 37.5 tons of urea and 9.3 tons of Di-ammonium phosphate (DAP).